Physical Education Teachers and Emergency Services: Training in prevention and key first aid to improve the use of emergencies - Lafuente, Jorge Carlos; González Raboso, Jessica; González-Raboso, Aida (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This article analyzes the perceptions of Physical Activity and Sports Science students about the training of Physical Education teachers in first aid and its relationship with the use of emergencies. A qualitative methodology has been used in which the collective interview was used. The results showed that teachers are responsible for assessing the severity of an injury, transferring or advising the use of the emergency service. The selection of exercises among others would improve accident prevention. Lastly, training in first aid is pointed out as deficient.